Neuronal Ca2+ sensor-1 contributes to stress tolerance in cardiomyocytes via activation of mitochondrial detoxification pathways. (October 2016) - Nakamura, Tomoe Y.; Nakao, Shu; Wakabayashi, Shigeo
Abstract: Identification of the molecules involved in cell death/survival pathways is important for understanding the mechanisms of cell loss in cardiac disease, and thus is clinically relevant. Ca 2+ -dependent signals are often involved in these pathways. Here, we found that neuronal Ca 2+ -sensor-1 (NCS-1), a Ca 2+ -binding protein, has an important role in cardiac survival during stress. Cardiomyocytes derived from NCS-1-deficient ( Ncs1 −/− ) mice were more susceptible to oxidative and metabolic stress than wild-type (WT) myocytes. Cellular ATP levels and mitochondrial respiration rates, as well as the levels of mitochondrial marker proteins, were lower in Ncs1 −/− myocytes. Although oxidative stress elevated mitochondrial proton leak, which exerts a protective effect by inhibiting the production of reactive oxygen species in WT myocytes, this response was considerably diminished in Ncs1 −/− cardiomyocytes, and this would be a major reason for cell death. Consistently, H2 O2 -induced loss of mitochondrial membrane potential, a critical early event in cell death, was accelerated in Ncs1 −/− myocytes. Furthermore, NCS-1 was upregulated in hearts subjected to ischemia-reperfusion, and ischemia-reperfusion injury was more severe in Ncs1 −/− hearts. Activation of stress-induced Ca 2+ -dependent survival pathways, such as Akt and PGC-1α (which promotes mitochondrial biogenesis and function), was diminished in Ncs1 −/− hearts. Overall, these data demonstrate that NCS-1 contributes to stress tolerance in cardiomyocytes at least in part by activating certain Ca 2+ -dependent survival pathways that promote mitochondrial biosynthesis/function and detoxification pathways. Highlights: NCS-1 knockout rendered mouse hearts more susceptible to oxidative/metabolic stress. Re-expression of NCS-1 partially rescued cardiomyocytes from H2 O2 -induced toxicity ATP levels, mitochondrial respiration and protein levels were lower in KO myocytes. NCS-1 expression reversed early ΔΨm loss in KO myocytes induced by H2 O2 . Stress-induced cardioprotective pathways were inhibited in KO hearts and myocytes.